Crystalline phase, surface morphology and electrical properties of monovalent-doped Nd0.75Na0.25Mn1-yCoyO3 manganites - Ab Mannan, Nurhabibah Nabilah; Razali, Sufia Aqilah; Shamsuddin, Suhadir; Noh, Mohamad Zaky (UTHM Publisher, 2017)
Perovskite-type manganites Nd0.75Na0.25Mn1-yCoyO3 (y = 0 – 0.05) have been investigated to clarify the influence of Co-doped on crystal phase and morphological study as well as electrical transport properties. The Nd0.75Na0.25Mn1-yCoyO3 samples are prepared via solid state synthesis method. X-ray diffraction analysis revealed all the samples are essentially single phased and the peaks are indexed to an orthorhombic structure with Pnma space. The morphological study from scanning electron microscope shows the improvement of the grains boundaries and sizes as well as the compaction of particles can be seen as cobalt doping increased. On the other hand, the temperature dependence of electrical resistivity measurements using four-point-probe technique indicates all samples maintained an insulator like behaviour down to low temperature. Analysis of the resistivity change with respect to temperature, dlnρ/dT-1 versus T reveals a slope changes of resistivity has been observed and a boarder peak exist for y = 0 sample and the peaks become significantly obvious for y = 0.02 and 0.05 samples. The peaks are observed in the range of charge ordering (CO) transition indicate the existence of CO in the system.